Berry Abscission in Vitis vinifera L. cv. Waltham Cross: Changes in Abscission-related Factors during Berry Development - Burger, D.A.; Jacobs, G.; Huysamer, M.; Taylor, M.A. (South African Journal of Enology and Viticulture, 2017)
During the 1999 season, changes in total soluble solids (TSS), titratable acids (TA), pedicel diameter, berry diameter, berry mass and fruit removal force (FRF) were determined at biweekly intervals from 27 until 111 days after full bloom (DAFB) for Waltham Cross table grapes. In addition, at each assessment stage, grape bunches were detached and held in the dark at about 25°C for 80 h. Thereafter, moisture loss, FRF, berry abscission potential as well as percentage berry abscission were determined. During stages I and II of fruit growth (27 to 54 DAFB), TSS did not change significantly, while TA increased. FRF increased significantly during this early stage of berry development, indicating a strengthening of the abscission zone tissue. During stage III (after 54 DAFB), a decline in FRF occurred, which coincided with a perceptible increase in TSS and a decrease in TA. Berry mass increased significantly from 27 to 111 DAFB. Pedicel diameter only increased significantly for the period 27 to 41 DAFB, while berry diameter increased significantly for the period 27 to 97 DAFB. Grapes sampled at 27 DAFB had a significantly lower FRF and significantly higher levels of berry abscission and moisture loss after the 80-hour period in the dark, compared with grapes sampled at a later stage. At 27 DAFB, the abscission zone developed between the pedicel and the rachis, thereafter it developed between the pedicel and the berry. Although FRF did not change significantly as berries ripened (from 83 to 111 DAFB), abscission potential and percentage berry abscission were significantly higher for grapes harvested at 83 DAFB at a TSS of 12.3°Brix than for grapes harvested more mature, at a higher TSS. Moisture loss correlated significantly (P<0.0001) with berry abscission, with a correlation coefficient of 0.84. Berry abscission also correlated significantly (P<0.0001) with abscission potential, pedicel and berry diameter, FRF (at sampling), FRF (after 80 h) and berry mass, but not with TSS or TA.